HUBUNGAN SUPERVISI PENGAWAS TERHADAP KINERJA DAN PROFESIONALISME GURU BIDANG STUDI FISIKA PADA SMA TELADAN WAY JEPARA - sugiono sugiono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
The supervision of the development activities planned to help teachers and school employees to do the job effectively. And the performance of teachers in the learning process are: Perform or teachers' skills in creating an atmosphere of educational communication between teachers and learners that includes the atmosphere of cognitive, affective and psychomotor as an attempt to learn planning by something to the stage of evaluation and follow-up to achieve the goal of teaching , Teacher professionalism is the commitment, where teachers are really committed to the teaching profession. Based on the concept above means regulatory oversight, dealing with the performance, supervision related to teacher professionalism